In the Community An Intermediate Integrated Skills Textbook (Open textbook library., 2016)
With funding from Alberta Open Educational Resources, Bow Valley College and NorQuest College collaborated to create Open Educational Resources (OER) in the form of e-textbooks for English language learners. NorQuest College created In the Community: An Intermediate Integrated Skills Textbook. The textbook: helps learners notice, learn, and practice English that will be helpful in your community gives learners practice in the four main language skills–listening, speaking, reading, and writing helps learners learn about intercultural skills helps learners develop some important essential skills can be used as an online textbook with interactive activities or downloaded, printed and used as a regular textbook The textbook is aimed at Canadian Language Benchmarks levels 5/6 and has been designed to be facilitated by an instructor.